DESIGN, FABRICATION AND TESTING OF A LAB-SCALE HYBRID MOBILE COOLING SYSTEM FOR OYSTER INDUSTRY - Yulai YANG; Xuejun QIAN; Marc J Louise CABALLES; Seong LEE (Journal of Construction Project Management and Innovation)
Cooling system is critical to maintain freshness of oysters and avoid contamination by bacteria. However, there is no persistent and efficient temperature control mechanism for cooling and storing of oysters in its supply chain from oyster farmer to the end consumers (e.g., market, restaurants). The aim of this project is to design, fabricate, and evaluate a lab-scale hybrid mobile cooling system for oyster aquaculture. This innovative hybrid cooling system integrated 110 volts AC cooling unit and 12 volts DC cooling unit with six individual chambers. These special features it to work under different power source. Even after power off, it can still run for several hours with battery (i.e., outage). So, it can be moved from boat to customers without change the storage condition of oysters. Six individual chambers have a potential to reduce energy loss and improve cooling performance because removing oyster baskets from one chamber will not affect temperatures in the other chambers. In this study, cooling system was fabricated in the laboratory based on the 2D design and 3D model. The performance of this cooling system was tested under various air circulation conditions (e.g., no vent open, two vents open, two vents open and air circulation fan on). Both cooling speed and the stand deviation of chamber temperature were used to evaluate the system cooling performance. Results indicated that the additional of air fan and two open vents in the divider has better cooling performance than the other two operating conditions. Hybrid cooling system with two vents and air circulation fan on can effectively cool down the oyster temperature from 21.1 º C to 5.6 º C within three hours. The stand deviation of the temperatures in six individual chambers can be reduced to 0.83 º C in four hours.